Literary Texts as the Material In Teaching Reading Comprehension - Davy Budiono (Magister Scientiae, 2010)
In selecting the appropriate literary texts to be used as the material in teaching reading comprehension, we have to consider a number of criteria. The criteria for valid literary texts to be used in teaching reading comprehension are the types of the literary texts, the students’ proficiency level, and the themes that will suit the students’ interest. Still, the teacher’s creativity in developing the material is still needed to support the achievement of the teaching-learning goals. This paper is intended for selecting the suitable literary material for teaching reading comprehension for the third year of SMU students. This paper begins with the discussion of the purposes of using literary texts in teaching reading comprehension. It is followed by the nature of literary texts and the nature of reading comprehension. Later in this paper the criteria of texts selection will also be discussed